ANALISIS KEPUASAN KINERJA KARYAWAN PADA BERDIKARI KOFFE MAGELANG - Yudhan, Muhammad Ilham; Sasana, Hadi (Transpublika Publisher, 2022)
In a company, employee performance is one of the determining components of company performance. The object used by researchers is a business that is currently popular, namely a coffee shop. As evidenced by the increase in coffee shops and domestic coffee consumption over the past three years. This study aims to analyze performance satisfaction and its impact on employees who work in coffee shops. This research uses a type of qualitative method research. The sampling technique used was a workman who worked at the coffee shop who was positioned as a barista. Sampling with respondents 2 barista employees from 4 baristas. Interviews are a means of analyzing the 2 baristas. The results of the study stated that compensation, benefits, promotions, awards and colleagues quite gave a good impression of employee engagement because in fact, according to employees who work at the coffee shop, they prioritize comfort and a relaxed environment. Employee attachment has a positive influence on employee performance. Because of the close attention and sense of family between the employee and the coffeshop owner. According to employees, this is what makes their performance better and to achieve their dreams and desires in the future. Hence, Berdikari Koffee set the system of working part time.